2011
DOI: 10.1097/wno.0b013e31820c4421
|View full text |Cite
|
Sign up to set email alerts
|

Statin or Nonsteroidal Anti-Inflammatory Drug Use Is Associated With Lower Erythrocyte Sedimentation Rate in Patients With Giant Cell Arteritis

Abstract: Statin use and NSAID use were associated with a lower ESR; however, they were not associated with lower CRP values. Clinicians should be aware that statin or NSAID use is associated with lower ESR in patients with GCA, and this test may therefore have lower sensitivity and specificity for recognizing patients with GCA, and CRP may be a superior test to evaluate patients for GCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…However the number of patients receiving statins in the study by Hegg et al was small (24/161 patients with GCA), and most of the patients received concomitant statins and NSAIDs (19/24). Therefore, it was difficult to draw conclusions regarding the role of NSAIDs or statins on levels of inflammatory markers in the study reported by Hegg et al (26). …”
Section: Discussionmentioning
confidence: 97%
“…However the number of patients receiving statins in the study by Hegg et al was small (24/161 patients with GCA), and most of the patients received concomitant statins and NSAIDs (19/24). Therefore, it was difficult to draw conclusions regarding the role of NSAIDs or statins on levels of inflammatory markers in the study reported by Hegg et al (26). …”
Section: Discussionmentioning
confidence: 97%
“… 19 The anti-inflammatory properties of statins are also evident in reducing the level of erythrocyte sedimentation rate in patients with GCA. 20 Statin use during the course of GCA facilitates more rapid tapering of prednisolone dose. 10 Furthermore, the anti-inflammatory effect of statins may be due to reduction of CD4+CD28 null T lymphocyte levels 21 and reduction of tumour necrosis factor-alpha or interlukin 6 levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, CRP and ESR do not have enough specificity for each pathway and are elevated in all of them, so we cannot recognize which one was responsible. Furthermore, some pain killers like NSAIDs (nonsteroidal anti-inflammatory drugs), usually taken by TAO patients, can influence the result of ESR [153].…”
Section: Controversial Biomarkersmentioning
confidence: 99%